Filsafat Kenabian Ibnu Sina dan Murtadha Muthahhari - Nurilaahii, Farhan (Jurnal Riset Agama, 2022)
The purpose of this study is to discuss the philosophy of prophethood according to Ibn Sina and Murtadha Mutahhari. The method used in this research is the library method with a qualitative approach. Sources of data used in this study are primary data in the form of books written directly by Ibn Sina and Murtadha Mutahhari, and secondary data in the form of books, journals, documents, and others related to the object under study. The results of this study are differences of opinion regarding the concept of prophethood, according to Ibn Sina, humans are humans who have obtained divine power in the form of divine intuition given by God to the human He chooses. Meanwhile, according to Murtadha Mutahhari, the Prophet is a human being chosen by God to guide mankind and every Prophet has his characteristics. Among the characteristics of the Prophet are miracles, infallibility, guidance from Allah, noble goals, constructive, striving, and possessing human values, and having revelations in the form of holy books. This research is expected to have a contribution both theoretically and practically. Theoretically, this research is expected to provide insight into the treasures of Islamic scholarship, while practically it is expected to provide benefits for research readers.